2023
DOI: 10.3389/fpls.2022.1096685
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling disclosed the effect of single and combined drought and heat stress on reprogramming of genes expression in barley flag leaf

Abstract: Despite numerous studies aimed at unraveling the genetic background of barley’s response to abiotic stress, the modulation of the transcriptome induced by combinatorial drought and increased temperature remains largely unrecognized. Very limited studies were done, especially on the flag leaf, which plays an important role in grain filling in cereals. In the present study, transcriptome profiles, along with chlorophyll fluorescence parameters and yield components, were compared between barley genotypes with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 107 publications
4
17
1
Order By: Relevance
“…It was observed that the number of genes specifically upregulated in flc mutants under the combination of salinity and heat were significantly higher (817) than those found in Wt (547) (Tables S6 and S7). This observation has been extensively reported by other researchers and highlights the importance of studying abiotic stress in combination (Lopez‐Delacalle et al., 2021; Mikołajczak et al., 2022; Rivero et al., 2014; Zandalinas, Rivero, et al., 2016). A GO enrichment analysis based on the biological processes affected showed that in both genotypes, genes related to RNA modification and protein folding were significantly enriched (Table S10).…”
Section: Resultssupporting
confidence: 80%
“…It was observed that the number of genes specifically upregulated in flc mutants under the combination of salinity and heat were significantly higher (817) than those found in Wt (547) (Tables S6 and S7). This observation has been extensively reported by other researchers and highlights the importance of studying abiotic stress in combination (Lopez‐Delacalle et al., 2021; Mikołajczak et al., 2022; Rivero et al., 2014; Zandalinas, Rivero, et al., 2016). A GO enrichment analysis based on the biological processes affected showed that in both genotypes, genes related to RNA modification and protein folding were significantly enriched (Table S10).…”
Section: Resultssupporting
confidence: 80%
“…However, in the embryonal axis, the expression of this gene and the change in its protein level induced by abiotic stresses has not been investigated so far. Although the function of ns-LTP2 proteins has not been fully described, the results presented in this work, combined with those obtained by others [ 15 , 58 ], may lead to the conclusion that the expression of barley ns-LTP2 genes is subject to tissue-specific regulation. Apart from the genes belonging to ns-LTP2 expressed in the leaf or root, ns-LTP2 .…”
Section: Discussionsupporting
confidence: 63%
“…Barley ns-LTP2 group consists of eight members [ 18 ], but each of them appears to be expressed in different tissues, for example Mikołajczak [ 58 ] identified three ns-LTP2 -like genes ( ns-LTP2 . 4 , ns-LTP2 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was clear from our results that the combination of salinity and heat induced a specific transcriptome response, in both Wt and flc mutants, which was completely different from that observed under salinity or heat applied individually, with 992 and 1243 specific DEGs, respectively (Figure 2a; Tables S5-S7). This observation has been extensively reported by other researchers, and highlights the importance of studying abiotic stress in combination (Rivero et al ., 2014; Zandalinas, Rivero, et al ., 2016; Lopez-Delacalle et al ., 2021; Mikołajczak et al ., 2022). However, from the specific DEGs found under the combination of salinity and heat, only 132 genes were common to Wt and flc mutants, which indicated a specific transcriptional reprogramming for ABA-deficient tomato plants, which still showed 1110 DEGs that were specifically regulated under these conditions (Figure 2a; Table S7).…”
Section: Resultsmentioning
confidence: 99%